Autonomous space systems control incorporating automated maneuvers strategies in the presence of parameters uncertainties. (May 2016) - Mazinan, A.H.; Shakhesi, S.
Abstract: The research attempts to deal with the autonomous space systems incorporating new automated maneuvers strategies in the presence of parameters uncertainties. The main subject behind the investigation is to realize the high-resolution small amplitude orbital maneuvers via the first control strategy. And subsequently to realize the large amplitude orbital maneuvers via the second control strategy, as well. There is a trajectory optimization to provide the three-axis referenced commends for the aforementioned overactuated autonomous space system to be able to transfer from the initial orbit to its final ones, in finite burn, as long as the uncertainties of key parameters of the system such as the thrust vector, the center of the gravity, the moments of the inertia and so on are taken into real consideration. The strategies performances are finally considered through a series of experiments and a number of benchmarks to be tangibly verified. Highlights: A number of automated maneuvers strategies are designed. A set of parameters uncertainties of the system are considered. A trajectory optimization is proposed to deal with the orbital process. A series of experiments are carried out to verify the investigated outcomes.